Biomass use trade-off in cereal cropping systems in the developing world : overview - Erenstein, Olaf; Gérard, Bruno; Tittonell, Pablo Adrian (2017)
Agricultural systems variously produce food, feed, fiber, fuel, and environmental goods. The relative emphasis varies over space and time – associated inter alia to inter-related developments in demand, technology and policy. Cereal cropping systems in the developing world traditionally emphasize food production with residual agricultural biomass (or crop residues) as an important by-product. Crop residues often have multiple uses such as livestock feed, household fuel source, soil amendment, construction and/or marketed for cash income. A number of trade-offs exist between these biomass uses, often reinforced by emerging drivers such as demographic pressure, increasing demand for livestock products and the development of fodder markets. In addition, there are recent developments, such as the increasing advocacy of conservation agriculture practices. Conservation agriculture calls for the retention of substantial crop residues as mulch in the field, thereby often competing with prevailing uses such as animal feed and/or conflicting with established crop management practices. There is also increasing advocacy for second generation biofuels (ethanol production from hemi-cellulosic material) – albeit that for now these are unlikely to have substantial short term implications for most smallholders across large swathes of the developing world as biofuel use is primarily limited to traditional biofuel uses and mainly informal and small scale